Blood micro-circulation state as a marker of the human body reserve capabilities to perform physical activity - Guryanov, M.; Bocharin, I.; Romanova, E.; Pozdeeva, A.; Kolokoltsev, M.; Limarenko, O.; Balashkevich, N.; Faleeva, E.; Tyupa, P.; Aganov, S. (Journal of Physical Education and Sport, 2023)
Reserve body capabilities and human health state assessment at the early stages of genesis is an urgent problem not only in clinical practice, but also in the field of physical education and sports. Purpose: application of the technique of laser Doppler flowmetry in physical education classes for the study of blood micro-circulation in students with health abnormalities.